Oral Administration of Multistage Albumin Nanomedicine Depots (MANDs) for Targeted Efficient Alleviation of Chronic Inflammatory Diseases. (13th January 2023) - Zhang, Fangke; Du, Yawei; Zheng, Jiancheng; Cai, Zhengwei; Ding, Tao; Zhuang, Pengzhen; Yang, Ding; Liao, Fangling; Zhang, Yu; Yang, Wu; Xiao, Yafang; He, Weiling; et al.
Abstract: Methotrexate (MTX) by oral taking has been employed as the first‐line medication for various chronic inflammatory diseases treatment, such as Crohn's disease and rheumatoid arthritis (RA). However, the oral administration of MTX has very limited clinical benefits and will be discontinued due to the suboptimal response and severe adverse effects on intestinal mucosa. Herein, a multistage albumin nanomedicine depot (denoted as MAND) is formulated by encapsulating MTX‐loaded human serum albumin nanoparticles (MTX@HSA NPs) into calcium alginate chitosan microcapsules using a gas‐shearing technology. The MANDs can provide protection to MTX@HSA NPs with well‐persisted biologic activity against gastric acid erosion and realize specific boost release of MTX@HSA NPs in the intestinal tract in response to the mild basic circumstance. The MTX@HSA NPs absorbed by intestine can selectively accumulate in inflammation lesion by exploiting the inflammation targeting ability of HSA. In the animal experiments, the MANDs show improved therapeutic efficacy for the treatment of both RA and colitis with minimized intestinal side effects in respect to the free MTX by oral administration. Therefore, this conceived oral MANDs can promote a more clinic popularity and enhanced benefits of MTX for the treatment of chronic inflammatory diseases. Abstract : Inspired by the chronic inflammatory microenvironment of autoimmune diseases, MTX@HSA NPs are encapsulated in calcium alginate chitosan using the gas‐shearing technology to engineer a multistage albumin nanomedicine depot (denoted as MAND) that can resist gastric acid erosion and burst in the intestinal tract for improving effect of chronic inflammatory diseases.